Salman Rushdie: The Accidental Intellectual in the Mediascape - Mendes, Ana Cristina (2018)
After Iran’s spiritual leader, Ayatollah Khomeini, issued an edict against the author of The Satanic Verses in 1989, calling for the execution of the Indianborn British citizen Salman Rushdie, the novel soon became politicized and its reception polarized. Rushdie’s text admits no supernatural quality to revelation and refers to Muhammad as “a false prophet,” and was thus considered a blasphemy. Eighteen years after the fatwa, the announcement of Rushdie’s knighthood in 2007 for his contribution to literature in the Queen’s birthday honours revived the earlier explosions of indignation. The acrimony that emerged primarily from British and South Asian Muslims, both in the late 1980s and 2000s, was perhaps intensified by the fact that Rushdie was born into a Muslim family in Bombay, then British India, a mere couple of months before the Partition of the subcontinent in 1947. While the question of freedom of speech has been central to Rushdie’s engagement with the media and his role as a public intellectual, he has been openly (and ambivalently) downplaying the relevance of politics to his literary writings. It is probably in Joseph Anton that Rushdie provides the most straightforward answer to the apparent paradox of the conflicted relationship between his literary writing and politics. In fact, a reflection on the apparent inner dialectic between Rushdie’s creative and political sensibilities has persisted throughout his texts, including those that will be mentioned in this chapter besides The Satanic Verses and Joseph Anton, such as the novels Midnight’s Children and Haroun and the Sea of Stories, as well as the essays and critical pieces included in the collection Imaginary Homelands.